1980
DOI: 10.1111/j.1745-4603.1980.tb00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Other Hydrocolloids on the Texture of Kappa Carrageenan Gels1

Abstract: The effect of different hydrocolloids on the breaking strength, cohesiveness and rigidity of kappa carrageenan gels was studied using comression tests with the Instron. Instrumental measurements were supplemented with benchtop sensory evaluation of texture by mouth, gel clarity and syneresis. The evaluated hydrocolloids included locust bean gum, iota carrageenan, amidated low methoxyl pectin, xanthan gum, and their selected combinations. Best gels were obtained by using 0.15% kappa carrageenan and 0.85% iota c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
6
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 5 publications
5
6
0
Order By: Relevance
“…Figures 2 and 3 show the curves obtained for the effect of gelatin concentration on the breaking strength and firmness of the gels, respectively. This shows, as found in previous studies (Szczesniak and MacAllister 1964;Kame1 and deMan 1977;Christensen and Trudsoe 1980;Munoz et al 1986), an increase in mechanical properties of the system as the gelatin concentration increased with the gels becoming firmer and stronger with increasing gelatin concentration. The figures also show the effect of adding 10 w/w% of sucrose.…”
Section: Melting Point Of Gelssupporting
confidence: 87%
“…Figures 2 and 3 show the curves obtained for the effect of gelatin concentration on the breaking strength and firmness of the gels, respectively. This shows, as found in previous studies (Szczesniak and MacAllister 1964;Kame1 and deMan 1977;Christensen and Trudsoe 1980;Munoz et al 1986), an increase in mechanical properties of the system as the gelatin concentration increased with the gels becoming firmer and stronger with increasing gelatin concentration. The figures also show the effect of adding 10 w/w% of sucrose.…”
Section: Melting Point Of Gelssupporting
confidence: 87%
“…Compression, shear and puncture measures ( Fig. 2a, b, c, respectively) showed that yield and maximum forces increased with increasing concentration of gelatin in agreement with previous studies (Ferry 1948;Szczesniak and MacAllister 1964;Kramer and Rosenthal 1965;Robinson et al 1975;Kame1 and deMan 1977;Christensen and Trudsoe 1980). Gelation theories suggest that the concentration of gelatin directly C. Puncture to 90% deformation influences intermolecular linkages forming the gel network Ward and Saunders 1958;Szczesniak and MacAllister 1964) and hence increases the gel firmness and the forces needed to deform it.…”
supporting
confidence: 88%
“…If the term signifies the distance that the gel deforms before breaking (not the amount of force required to break the gel) as gelatin concentration is increased, few differences would occur. This is verified by mechanical cohesiveness values (Table 1) and by other gel studies (Christensen and Trudsoe 1980). Although manual cohesiveness was correlated with yield deformation at 50 m d m i n (r = 0.88, p < 0.05, df = 3), the sensory data suggest that the term "cohesiveness" may have been misunderstood, as the responses resembled the firmness data.…”
supporting
confidence: 72%
“…Gelation of kappa-and iotacarrageenan occurs in the presence of cations such as K', Ca", or NH,', each of which produces gels with different textures (Guiseley et al 1980). Whereas iota-carrageenan produces transparent and elastic gels which resemble gelatin gels, kappacarrageenan tends to form brittle gels due to traces of calcium (Christensen and Trudsoe 1980).…”
Section: Introductionmentioning
confidence: 99%